Deposition of Sediment in Detention Pond-Laboratory Study - Tarmizi Ismail, 1964-, author 553228; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Awam 8450 (Johor Bahru, Johor : PENERBIT UTM PRESS, 2008)
Suspended sediment is the pollutant of primary concern to the urban rivers that results in adverse environmental and economical effect. Detention pond may become the structure that can be indirectly used to remove a portion of suspended sediment. Although the ponds were initially designed to control the increased quantity of runoff associated with impervious areas in the urban landscape, the ponds have been increasingly used to reduce the concentration of contaminants in the runoff. Experiments on deposition of sediments in detention pond and other related aspects such as sediment concentration dispersion and efficiency of the pond were investigated in this study.